2015
DOI: 10.1159/000438724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of IgE Responses to Der p 1 and Der p 2 in Chinese House Dust Mite-Allergic Patients

Abstract: Background: The role of specific IgE (sIgE) against Der p 1 and Der p 2 in Chinese patients with house dust mite (HDM) allergy has not yet been well investigated. Methods: Onehundred patients were enrolled, based on sensitization and doctor-diagnosed allergy to HDM. Questionnaires were administered to document demographic and clinical characteristics. Serum IgE reactivity to Dermatophagoides pteronyssinus (Dp) extract, Der p 1, Der p 2 and Der p 10 was measured by ImmunoCAP. Results: Almost all patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
(40 reference statements)
4
14
0
Order By: Relevance
“…The close correlation between serum IgE titters against Der p1, Der p2 and Der p23, on the one hand, and against D. pteronyssinus on the other, further supports the dominant role of these allergensin the human IgE response against HDM in our area. We also measured IgE against Der p 10 in 63 patients, and5 (8.33%) of them had detectable levels of IgE against this allergen, showing a higher prevalence compared to earlier works from China [39,40].The IgE response against Der p2 and Der p23 represented a larger fraction compared to Der p 1 as shown by former reports in Spain [41]. Mean specific IgE responses to Der p2 and Der p1 allergens were higher to those elicited to Der p23 in terms of quantity.…”
Section: Discussionmentioning
confidence: 78%
“…The close correlation between serum IgE titters against Der p1, Der p2 and Der p23, on the one hand, and against D. pteronyssinus on the other, further supports the dominant role of these allergensin the human IgE response against HDM in our area. We also measured IgE against Der p 10 in 63 patients, and5 (8.33%) of them had detectable levels of IgE against this allergen, showing a higher prevalence compared to earlier works from China [39,40].The IgE response against Der p2 and Der p23 represented a larger fraction compared to Der p 1 as shown by former reports in Spain [41]. Mean specific IgE responses to Der p2 and Der p1 allergens were higher to those elicited to Der p23 in terms of quantity.…”
Section: Discussionmentioning
confidence: 78%
“…9 Wang et al showed that Der p1 sensitization was more important in children, while Der p2 sensitization became more dominant in adults and after longer disease duration. 10 Our previous study has found that HDMs, and Der p in particular, are the major aeroallergens among AR patients in Central China, with a sensitization rate of over 90%. 11 Therefore, the aim of this study was to investigate the Der p molecular sensitization profile and its association with clinical manifestations of HDM-AR patients in Central China.…”
Section: Introductionmentioning
confidence: 94%
“…Component‐resolved diagnosis (CRD) enables IgE sensitization profiles and potential risk to be established, and whether specific IgE is the result of primary sensitization or cross‐reactivity can also be determined . Such information can assist in making the right choice of immunotherapy, particularly when pollen seasons of different allergenic sources overlap .…”
Section: Introductionmentioning
confidence: 99%